Teachers’ Professional Ethics and Instructional Performance as Correlates of Students’ Academic Performance in Secondary Schools in Owo Local Government, Ondo State, Nigeria - Ayeni, Adeolu Joshua (Advances in Social Sciences Research Journal, 2018)
The study investigated teachers’ compliance with professional ethics and instructional tasks performance, and determined the implication on students’ academic performance in secondary schools in Owo Local Government Area of Ondo State, Nigeria. Three research questions were raised and two hypotheses were formulated to guide the study. 90 top management officers (principals, vice principals, heads of departments, guidance and counselors, and examination officers completed questionnaire titled “Teachers Professional Ethics and Instructional Tasks Performance Questionnaire (TPEITPQ), and Students’ Academic Performance Profoma (SAPP) ) in nine (9) secondary schools using randomly sampling technique. Data were analyzed using frequency count, percentage, mean score and Pearson Product Moment Correlation Coefficient (PPMCC) at 0.05 level of significance. The findings revealed that there is a significant relationship between teachers’ professional ethics and instructional performance [r (88) = 0.872, p<0.05, also there is significant relationship between teachers’ instructional tasks performance and students’ academic performance [r (88) = 0.79, p<0.05). The level of teachers’ compliance with professional ethics was high in the components of: punctuality (68.9%), communication skill (63.3%), human relations (61.6%), effective time management (66.6%), adequate knowledge of subject matter (67.8%) and good dressing habit (81.2%). Further findings revealed that teachers prepare their lesson notes promptly (68.9%), conduct continuous assessment (73.3%), maintain good classroom management (66.7%), ensure students’ discipline (81.1%) and participate actively in committees’ work (75.6%). The level of students’ academic performance was above average. Based on the findings, it was concluded that principals should collaborate with other professional bodies to organize intensive and regular seminars/workshops for capacity development of teachers to enhance professional conduct. Also, the state government in collaboration with other relevant stakeholders in the education sector should create enabling environment to enhance teachers’ professional ethical standards and provide adequate learning facilities/materials to boost teachers’ instructional tasks performance and achieve better academic performance of students in secondary schools